Fast Food Purchase Behaviour in Botswana: An Exploratory Study - Makgosa, Rina; Mabalane, Nchenesi (Indian Journal of Marketing, 2011)
The current study is a preliminary investigation of perceptions that consumers in Botswana hold about fast-food restaurants in terms of health, convenience, price and service. A structured questionnaire was successfully administered to a sample of 185 consumers. Findings indicate that consumers in Botswana hold negative perceptions about fast-food restaurants with respect to health, price and the service they offer and positive perceptions about their convenience. Females also held stronger negative perceptions about the nutritional value of fast foods than males. Additionally, young and middle-aged consumers perceived fast-food restaurants as providing more convenience than older consumers. These results suggest that the managers of fast-food restaurants in Botswana need to amend consumers' negative perceptions of health, service, and price, while consistently reinforcing positive perceptions of convenience.